THE EFFECT OF CHANGES IN VALUE-ADDED TAX RATES (VAT) AND COST OF GOODS SOLD (COGS) ON SALES TURNOVER AT PT. VCS - Asah, Maranatha Kezya Beauty Caesaria; Widajantie, Tituk Diah (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
The increase in Value Added Tax (VAT) rates and the rise in Cost of Goods Sold (COGS) significantly impact the business strategy and profitability of the company. The research aims to examine the impact of the increase in VAT rate and changes in the Cost of Goods Sold on PT's business strategy and profitability. VCS. The method used is quantitative research using PT's sales data. VCS from 2018 to 2022, as the population was selected through a purposive sampling method. Data analysis was conducted using SPSS version 27. The research findings indicate that the increase in the value-added tax rate significantly impacts PT's sales revenue. VCS, while the increase in Cost of Goods Sold does not considerably affect the company's Sales Revenue